Prospective Madrasah Teachers' Scientific Competencies Integrated with Scientific Literacy through the STEM Approach - Rokhimawan, M. A.; Yuliawati, F.; Kamala, I.; Susilawati, S. (Jurnal Pendidikan IPA Indonesia, 2022)
This study aims to measure the scientific competence of prospective teachers of Madrasah Ibtidaiyah integrated scientific literacy through a STEM approach. The research method used was descriptive quantitative with a sample of 40 students from the same study program at two different universities. The selected sample has taken basic science courses with a minimum score of B. This research used a purposive sampling technique, where the sampling actively participates in learning activities. Data were collected using a set of instruments to analyze the prospective teachers’ scientific competence. The instruments were declared valid based on expert judgment and showed a Cronbach Alpha score of 0.68 before being used. Scientific competence data were obtained from the results before and after the essay, practicum, multiple-choice test, and questionnaire instruments. Data were analyzed descriptive quantitative using inferential statistics with a T-test. Inferential statistical analysis revealed differences in scientific competence of prospective madrasah teachers in Study Program A and Study Program B (t = 5.98 1.83). The measurement results of the test of science content mastery aspect with an average of 58.3 and 50.8. The practicum mastery of science process skills results from the problem-solving skills test are 48.4 and 39.6. From the questionnaire results on scientific literacy, students still need to improve their independence in studying science, scientific thinking skills, the ability to use scientific knowledge in problem-solving, and integrating the STEM approach. From the findings, it can be concluded that the analysis of the scientific competence of prospective madrasah teachers shows an apparent and significant difference. The prospective madrasa teachers’ scientific competence is needed to prepare students as prospective teachers who are STEM literate.